PENGARUH KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Atika Yuliani Saputri; Sulastri Sulastri; Samadi W Bakar (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2016)
This study aim to determine the influences of investment decision which measured by Current Assets to Total Assets Ratio (CATAR), Fixed Assets to Total Assets Ratio (FATA), Receivable to Total Assets Ratio (RTA), and Inventory to Total Assets Ratio (ITA) to free cash flow as an indicator of firm value on the manufacturing sub-sectors of food and beverages listed on Indonesia Stock Exchange, and the unit of analysis is 13 food and beverages industry listed on Indonesia Stock Exchange. The methods used in this research is quantitive method with multiple regression anlysis techniques. Based on the regression model test proves that the variation of the company can be expalined by the variable Current Assets to Total Assets Ratio (CATAR), Fixed Assets to Total Assets Ratio (FATA), Receivable to Total Assets Ratio (RTA), and Inventory to Total Assets Ratio (ITA) with coefficient of determination R square (R2) as 18,9%, with a significance value as 0,007. Analysis partially by t-test showed that the variables Inventory to total assets (ITA) has a significant effect on the firm value. While Current Assets To Total Assets Ratio (CATAR), Fixed Assets to Total Assets Ratio (FATA), Receivable to Total Assets Ratio (RTA) has not effect on the firm value. Keywords : firm value, CATAR, FATA, RTA,ITA